Clinical evaluation of feasibility and effectiveness using a virtual reality device during local anesthesia and extractions in pediatric patients - Pathak, Pradnya D.; Lakade, Laxmi S.; Patil, Krishna V.; Shah, Preetam P.; Patel, Alok R.; Davalbhakta, Rucha N. (European archives of paediatric dentistry, 2023)
Purpose Pediatric dentistry requires more than routine dental knowledge and skills in executing quality dental care. The quality of dental treatment is indirectly proportional to a child’s anxiety and fear. The recent distraction technique, the use of virtual reality (VR) devices has intrigued many researcher’s minds. Therefore, this study was conducted to assess the clinical feasibility and effectiveness of the VR device in reducing pain and anxiety in pediatric patients during mandibular primary molar extraction. Methods This research trial had 30 healthy children between the ages of 6 and 12 who required mandibular primary molar extraction. The subjects were divided into two groups using a simple randomization method. In the study group ( n = 15), extraction was carried out using a VR device, whereas, in the control group ( n = 15), extraction was carried out without the use of a VR device. Pre- and post-extraction anxiety levels were measured by Venham’s picture test (VPT) and the heart rate. After the procedure, pain and behavior were evaluated by the Wong-Bakers Faces pain rating scale (WBS) and FLACC Scale respectively. Results The pre-extraction values of the VPT and heart rate showed no statistically significant difference. This indicates that participants of both groups had a similar level of anxiety at baseline. There was a statistically significant increase ( p = 0.028) between pre- and post-heart rates in the control group, with no significant change in the study group. Conclusion The use of a virtual reality device in children can reduce anxiety during primary molar extractions as evaluated by heart rate. Virtual reality devices might be an adjunct to high-quality dental care and to other behavior management methods. Definitive outcomes can be attained by encouraging studies overcoming the present limitations, and considering salivary biochemical indicators for the assessment of these devices.